Current density effect on hydrogen permeation in PEM water electrolyzers. (25th May 2017) - Trinke, P.; Bensmann, B.; Hanke-Rauschenbach, R.
Abstract: Hydrogen permeation is an important phenomena for PEM water electrolyzers, due to several reasons as safety issues and efficiency loss. The present contribution deals with the measurement of hydrogen volume fraction within the anode product gas during PEM water electrolysis for different temperatures and cathode pressures. High cathode pressures lead to high anode hydrogen volume fractions close to the lower explosion limit of hydrogen in oxygen, which are caused by increased hydrogen permeation. It is shown that the results of the hydrogen volume fraction measurements can be easily converted into hydrogen permeation rates. Additionally, the experimental obtained permeation data indicate that hydrogen permeation increases linear with increasing current density. The impact of current density on the hydrogen permeation is very strong in comparison to the effects of temperature and pressure e.g. a current density increase of 1 A/cm 2 can causes a permeation increase comparable to a cathode pressure increase of 20 bar. In the second part of this contribution different theories to explain this strong dependence on current density are discussed. The most probable explanation is that due to mass transfer limitations a supersaturation of dissolved gas within the catalyst ionomer film arises that causes the investigated increase in permeation. Highlights: Hydrogen permeation increases linear with increasing current density. Increase of 1 A/cm 2 causes permeation comparable to 20 bar pressure difference. Local pressure enhancement cannot solely explain permeation increase with current. Gas supersaturation within the catalyst ionomer causes permeation increase.